2016
DOI: 10.21037/tau.2016.03.01
|View full text |Cite
|
Sign up to set email alerts
|

The devil is in the details: an analysis of the subtleties between phosphodiesterase

Abstract: Erectile dysfunction (ED) is a common sexual disorder with numerous etiologies involving multiple organ systems that leads to significant distress and decreased quality of life for the affected men. Fortunately, there are several modalities and interventions for treating ED. Oral medications, intra-urethral compounds, intracorporeal injections, vacuum-assist devices and surgically implanted prostheses are all part of the treatment algorithm. One of the first-lines and certainly the most widely used options for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…PDE5 inhibitors like sildenafil, tadalafil or vardenafil are used in the treatment of erectile dysfunction (Smith-Harrison et al 2016), but also to treat pulmonary hypertension (Ghofrani et al 2006) thereby exposing more and younger patients. Interestingly, long-term treatment with sildenafil did not change spontaneous contractility of the epididymis in a rat model (Mietens et al 2014).…”
Section: Pde Inhibitorsmentioning
confidence: 99%
“…PDE5 inhibitors like sildenafil, tadalafil or vardenafil are used in the treatment of erectile dysfunction (Smith-Harrison et al 2016), but also to treat pulmonary hypertension (Ghofrani et al 2006) thereby exposing more and younger patients. Interestingly, long-term treatment with sildenafil did not change spontaneous contractility of the epididymis in a rat model (Mietens et al 2014).…”
Section: Pde Inhibitorsmentioning
confidence: 99%
“… 11 , 28 , 29 , 30 Controlled trials and systematic reviews have shown that the response rates to that medication are almost 90%. 31 , 32 Because there is sound evidence in the literature demonstrating the efficacy and safety of PDE-5 inhibitors and other types of non-surgical treatment in men with SCI, we found it surprising that only a few patients had access to any sort of ED treatment. This fact might indicate that more attention should be addressed to this population of men with SCI and medical care providers.…”
Section: Discussionmentioning
confidence: 97%
“…The clinical efficacy and safety profile of PDE5i has been reported by numerous high-quality, well-designed, blinded, randomized controlled trials comparing PDE5i both to placebo and to other PDE5i drugs [3,4,5,6]. Overall, oral PDE5i in recommended doses is an effective medical therapy for ED with an excellent safety profile and is generally well tolerated.…”
Section: Current Standard Erectile Dysfunction Therapymentioning
confidence: 99%